2011
DOI: 10.11606/issn.1984-4867.v22i1p25-43
|View full text |Cite
|
Sign up to set email alerts
|

Enoturismo: experiências e sensações no Vale dos Vinhedos (RS)

Abstract: Wine Tourism: experiences and sensations in the Vale dos Vinhedos (RS) Turismo del Vino: experiencias y sentimientos en el Vale dos Vinhedos (RS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
7
0
10
Order By: Relevance
“…A wide range of publications have tried to understand this phenomenon focusing on different aspects such as the evolutionary point of view in wine regions (Alonso et al, 2008;Liu, 2011, 2012;Valduga, 2014); under the perspective of enotouristic itineraries, tourism planning and image of tourist destinations (Fuller, 1997;Getz, 2000;Williams, 2001;Bruwer, 2003;Sanders, 2004) and from the perspective of demand and marketing in wine tourism (Leiper and Carlsen, 1998;Getz et al, 1999;Hall et al, 2004;Brown and Getz, 2005;Bruwer and Alant, 2009;Simeon and Sayeed, 2011;Marzo Navarro and Pedraja Iglesias, 2012;Quadri-Felitti and Fiore, 2012;Silva, 2016). Another aspect that emerged is the experiential studies, based on the so-called Experience Economics of Pine II and Gilmore (1999), which goes against the emotional side of planning tourism experiences, sensations, innovation and creativity (Ali- Knight and Carlsen, 2003;Carini et al, 2005), and Caroline (2005), Nowak and Newton (2006), Roberts and Sparks (2006), Asero and Patti (2009), Tonini and Lavandoski (2011).…”
Section: Development In the Grape And Wine Region: Factors Of Change mentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of publications have tried to understand this phenomenon focusing on different aspects such as the evolutionary point of view in wine regions (Alonso et al, 2008;Liu, 2011, 2012;Valduga, 2014); under the perspective of enotouristic itineraries, tourism planning and image of tourist destinations (Fuller, 1997;Getz, 2000;Williams, 2001;Bruwer, 2003;Sanders, 2004) and from the perspective of demand and marketing in wine tourism (Leiper and Carlsen, 1998;Getz et al, 1999;Hall et al, 2004;Brown and Getz, 2005;Bruwer and Alant, 2009;Simeon and Sayeed, 2011;Marzo Navarro and Pedraja Iglesias, 2012;Quadri-Felitti and Fiore, 2012;Silva, 2016). Another aspect that emerged is the experiential studies, based on the so-called Experience Economics of Pine II and Gilmore (1999), which goes against the emotional side of planning tourism experiences, sensations, innovation and creativity (Ali- Knight and Carlsen, 2003;Carini et al, 2005), and Caroline (2005), Nowak and Newton (2006), Roberts and Sparks (2006), Asero and Patti (2009), Tonini and Lavandoski (2011).…”
Section: Development In the Grape And Wine Region: Factors Of Change mentioning
confidence: 99%
“…It was identified that the studies that deal with cooperative relations in winemaking (Giron, 1987(Giron, , 1996(Giron, , 2009Ribeiro, 2002;Valduga, 2011;Tonini and Lavandoski, 2011) do not contemplate new development perspectives focused on innovation and do not establish communication with the aspects of hospitality and tourism. This paper therefore seeks a theoretical approach for advancing the analysis of this context.…”
Section: Introductionmentioning
confidence: 99%
“…No conjunto de abordagens pela via experiencial, ganham corpo as pesquisas em enoturismo, muitas delas fundamentadas nos estudos da chamada Economia da Experiência de Pine II e Gilmore (1998). Algumas delas vertem para ao lado emocional da demanda do enoturismo, para o planejamento de experiências, sensações, criatividade e inovação (Ali -Knight & Carlsen, 2003;Carmichael, 2005;Nowak & Newton, 2006;Roberts & Sparks, 2006;Asero & Patti, 2009;Tonini & Lavandoski, 2011;Quadri -Felitti & Fiore, 2012;Capitello, Begalli & Agnoli, 2013;Bizinelli et al, 2014;Gravari -Barbas, 2014;Galvéz, Fernández e Lopez -Guzmán, 2015;, Manosso et al, 2016. Diante do exposto, pela periodização das fontes bibliográficas, pode -se sugerir que os estudos em enoturismo avançaram de um contexto amplamente descritivo da atividade nos anos 1990, abordando casos aplicados e de planejamento de rotas e roteiros e estudos de demandas para contextos mais simbólicos e experienciais, sejam da oferta, sejam da demanda em enoturismo.…”
Section: O Enoturismo Como Produto Turísticounclassified
“…(2010) comentam que as indicações geográficas destacam as particularidades não só do produto, mas também do território em que este se insere. Essa originalidade e características próprias podem ser atrativas aos turistas posto que o viajante "consome lugares" (sua cultura, seus recursos, o ambiente, a paisagem, entre outras possibilidades subjetivas) e busca cada vez mais experiências às quais possa atribuir significado e emoções decorrentes das características e vivências particulares ao lugar (Tonini & Lavandoski, 2011). Esse consumo pode se dar antes da viagem, por meio da degustação de um produto; durante a viagem, por meio de atividades relacionadas à produção; e após a viagem, com o prolongamento da mesma por meio dos souvenirs (Medeiros & Passador, 2015).…”
Section: Análise E Discussõesunclassified